Dispensing errors in Lebanese community pharmacies: incidence, types, underlying causes, and associated factors - Lama Soubra; Samar Karout (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Objectives: To assess the incidence, types, the causes of as well as the factors associated with dispensing errors in community pharmacies in Lebanon. Methods: An observational cross-sectional study was conducted in 286 pharmacies located all over Lebanon. Data were collected by senior pharmacy students during their experiential learning placement. Collected data included information on the types of dispensing errors, the underlying causes of errors, handling approaches, and used strategies for dispensing error prevention. Data were analyzed using multiple logistic regression to determine factors that were associated with dispensing errors. Results: In the twelve thousand eight hundred sixty dispensed medications, there were 376 dispensing errors, yielding an error rate of 2.92%. Of these errors, 67.1% (252) corresponded to dispensing near-miss errors. The most common types of dispensing errors were giving incomplete/incorrect use instructions (40.9% (154)), followed by the omission of warning(s) (23.6% (89)). Work overloads/time pressures, illegible handwriting, distractions/interruptions, and similar drug naming/packaging were reported as the underlying causes in 55% (206), 23.13% (87), 15.15 % (57), and 7% (26) of the errors respectively. Besides, high prescription turnover volume, having one pharmacist working at a time, and extended working hours, were found to be independent factors that were significantly associated with dispensing errors occurrence (p<0.05). Conclusions: This study sheds light on the need to establish national strategies for preventing dispensing errors in community pharmacies to maintain drug therapy safety, considering identified underlying causes and associated factors.